Developing Chairperson Networks at the State System Level - Cheryl L. Hochberg (Academic Chairpersons Conference Proceedings, 2016)
While many colleges and universities have local chair networks, few networks extend across state systems. These can be advantageous for chairs working under common bureaucracies and collective bargaining agreements for the purpose of training, mutual empowerment and advocacy for academic programs.
Keywords: State systems of higher education; chair networks; collective bargaining agreements; academic program advocacy; chair training